2020
DOI: 10.1073/pnas.1918145117
|View full text |Cite
|
Sign up to set email alerts
|

Robust landscapes of ribosome dwell times and aminoacyl-tRNAs in response to nutrient stress in liver

Abstract: Translation depends on messenger RNA (mRNA)-specific initiation, elongation, and termination rates. While translation elongation is well studied in bacteria and yeast, less is known in higher eukaryotes. Here we combined ribosome and transfer RNA (tRNA) profiling to investigate the relations between translation elongation rates, (aminoacyl-) tRNA levels, and codon usage in mammals. We modeled codon-specific ribosome dwell times from ribosome profiling, considering codon pair interactions between ribosome sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 103 publications
5
54
0
Order By: Relevance
“…Despite this, many efforts were made to create a comprehensive view of tRNA pools. Notably, the advent of high throughput methods to study tRNA levels has provided a greater understanding of tRNA landscapes in cells under different conditions [18][19][20][21][22]. A microarray-based approach has shown that tRNA pools differ among tissues in humans [23] and that there is a significant correlation between relative tRNA abundance and codon usage of highly expressed, tissue-specific genes [23].…”
Section: Major Determinants Of Translation Elongationmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite this, many efforts were made to create a comprehensive view of tRNA pools. Notably, the advent of high throughput methods to study tRNA levels has provided a greater understanding of tRNA landscapes in cells under different conditions [18][19][20][21][22]. A microarray-based approach has shown that tRNA pools differ among tissues in humans [23] and that there is a significant correlation between relative tRNA abundance and codon usage of highly expressed, tissue-specific genes [23].…”
Section: Major Determinants Of Translation Elongationmentioning
confidence: 99%
“…Codon content of a translatome is one of the factors contributing to the large variability and codon-dependent heterogeneity in ribosome elongation rates. Indeed, indirect estimates of ribosome dwell times obtained from yeast and mouse liver ribosome profiling datasets have shown that ribosome dwell times, that is the time spent by a ribosome on a specific position on a transcript, are strongly codon-specific [ 18 , 37 , 38 ]. The suggestion that frequently used codons are translated faster is frequent in the literature, in many organisms.…”
Section: Major Determinants Of Translation Elongationmentioning
confidence: 99%
See 3 more Smart Citations